Laparoscopic nephrectomy in children: Initial experience - Shankar Gowri; Babu Narendra; Ramesh S; Srimurthy K (Wolters Kluwer Medknow Publications, 2006)
Aims: Our objective was to evaluate the feasibility and efficacy of laparoscopic nephrectomy in infants and children. Materials and Methods: From 2000 to 2005, 28 children, aged 3 months to 14 years underwent laparoscopic nephrectomy, laparoscopic nephroureterectomy and heminephrectomy. Medical records were reviewed retrospectively for clinically relevant data. Results: There were no conversions. Mean operating time was 75 minutes and there were no intraoperative complications in our series. Cosmetic results were excellent in all cases. Average hospital stay was 4 days. Conclusions: Laparoscopic nephrectomy, laparoscopic nephroureterectomy and heminephrectomy may be safely performed in infants and children with minimal morbidity, post-operative discomfort and improved cosmesis.